Social Service Policy in Handling Beggars in Lhokseumawe City - Cut Sukmawati; Bambang Heru Prasatyo (Master Program of Sociology, Universitas Malikussaleh,, 2021)
Lhokseumawe City, in implementing PP No. 31 of 1980 on Tackling Homeless and Beggars and Qanun Aceh No. 11 of 2013 on Social Welfare authorizes Social Services in taking policies in handling beggars and homeless people. A total of 32 people in 2019 and 25 people in 2018 have been caught in raids by Social Services. This research used qualitative research method with descriptive type analysis. Data collection techniques were observation, interviews and documentation. The data obtained by the researchers were analyzed with several steps, namely data collection, data reduction, data presentation, and finally, the withdrawal of conclusions. The results showed that the social service policy in handling beggars in Lhokseumawe city has not been maximized; there are three stages in handling beggars, namely preventive, regressive and rehabilitative stages. Preventive Stage of Social Services provides assistance through programs that have been created to reduce the poor to beggars, the second stage of Refresive social services in collaboration with cross-sectoral such as Satpol Pamong Praja (PP) and Wilayatul Hisbah (WH) conduct raids on beggars and at the Rehabilitative stage social services have not been able to do so, only giving direction and guidance not to beg anymore. But all measures have not been able to reduce the number of beggars. Barriers in the handling of beggars are divided into two, namely internal and external. Internal, it is the absence of a legal umbrella for social services in sanctioning beggars, while externally; it is from the beggars themselves who do not want to listen to the direction and guidance of social services not to beg anymore.